Edukasi Bahaya Penyalahgunaan Obat sebagai Upaya Preventif pada Siswa Sekolah Menengah Atas - Fifin Oktaviani; Helda Muliana; Heldi Candra (Universitas 17 Agustus 1945 Semarang, 2026)
Substance and prescription drug misuse among adolescents continues to escalate and demands targeted preventive strategies within the school setting. This community service activity aimed to enhance students’ knowledge about the hazards of drug abuse through an interactive, school-based educational intervention. The program was conducted on 11 November 2026 at SMA Negeri 7 Kota Batam, involving fifty grade-X students as participants. A pre-experimental one-group pretest–posttest design was employed. The intervention combined interactive lectures, real-case illustrations, and two-way discussion, with knowledge measured using a content-validated questionnaire covering ten indicators. The mean score improved from 55.2 (pretest) to 86.3 (posttest), a gain of 31.1 points, while the proportion of correct answers across indicators rose from 48.6-62.9% to 80.0-91.4%. The largest gains appeared on items concerning rational drug use and the importance of professional health guidance, whereas the legal-consequence indicator improved more modestly. Interactive, contextually relevant education proves effective in elevating adolescent knowledge of drug abuse hazards, with stronger gains on experience-near content than on abstract regulatory aspects.